Automated Web-Based Curriculum Vitae System with QR Code Integration for Portfolio Access - Setiawan, Wahyu Fajar; Shanty, Ratna Nur Tiara; Swastyastu, Cempaka Ananggadipa (STMIK Banjarbaru, 2024)
In the current digital era, the importance of crafting compelling Curriculum Vitae (CV) and presenting portfolios has escalated across various professional domains. This research introduces a pioneering solution, an automated information system designed to empower users to seamlessly create CVs and access portfolios through a dedicated website. The system facilitates a user-friendly process wherein individuals can register, input their CV and portfolio data, choose from a variety of templates, and generate a personalized CV embedded with a QR code. This QR code serves as a convenient link, providing instant access to the individual's comprehensive portfolio. Notably, the system is not confined to personal use, as users can effortlessly share their CVs and portfolios with others by distributing the QR code. The integration of web technology, QR codes, and a diverse range of templates constitutes a novel approach, enhancing both the efficiency and quality of CV compilation and portfolio presentation. This research aims to address the evolving needs of professionals by offering a streamlined and technologically advanced solution for managing career profiles. By combining innovative features, such as QR code integration, with the flexibility of template selection, the system seeks to redefine the standards of CV creation and portfolio management, making the entire process more accessible and efficient.Kata kunci: Curriculum Vitae; Portfolio; Resume builder; Career profile management; Web technology Â AbstrakDi era digital saat ini, pentingnya membuat Curriculum Vitae (CV) yang menarik dan menampilkan portofolio telah meningkat di berbagai bidang profesional. Penelitian ini memperkenalkan solusi inovatif berupa sebuah sistem informasi otomatis yang dirancang untuk memberdayakan pengguna membuat CV dan mengakses portofolio dengan mulus melalui situs web khusus. Sistem ini memfasilitasi proses yang mudah digunakan di mana individu dapat mendaftar, memasukkan data CV dan portofolio mereka, memilih dari berbagai templat, dan menghasilkan CV yang dipersonalisasi dengan kode QR. Kode QR ini berfungsi sebagai tautan yang nyaman, memberikan akses instan ke portofolio lengkap individu tersebut. Khususnya, sistem ini tidak terbatas untuk penggunaan pribadi, karena pengguna dapat dengan mudah membagikan CV dan portofolio mereka dengan orang lain dengan menyebarkan kode QR. Integrasi teknologi web, kode QR, dan beragam templat merupakan pendekatan baru yang meningkatkan efisiensi dan kualitas pembuatan CV serta presentasi portofolio. Penelitian ini bertujuan untuk menjawab kebutuhan profesional yang terus berkembang dengan menawarkan solusi yang efisien dan berteknologi maju untuk mengelola profil karier. Dengan menggabungkan fitur inovatif, seperti integrasi kode QR, dengan fleksibilitas pemilihan templat, sistem ini berupaya untuk mendefinisikan ulang standar pembuatan CV dan pengelolaan portofolio, membuat seluruh proses lebih mudah diakses dan efisien.Â